PERBEDAAN INTENSI BERWIRAUSAHA BERDASARKAN LOKUS KENDALI PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - Apriliyanti, A; Zain, Nuryetty (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2014)
Writing this script has purpose to get valid and reliable data or fact, to know more the difference Entrepreneurial Intention based Locus of Control in the Students of the Faculty of Economic Universitas Negeri Jakarta. This research during three months during March until May 2014. This research used survey method with Causal Comparative Approach and using primary data (Locus of Control and Entrepreneurial Intention). The sampling technique in this research using Simple Random Sampling technique with 172 respondents in the sample, 133 students are classified to Internal Locus of Control and 39 students are classified in the External Locus of Control. The research Method in survey method with causal comparative approach. Used this method because for get reliable data and correct to fact and actual from the resource. Entrepreneurial Intention data using instrument Likert scale. Data processing is done using Microsoft Excel Program. Before that is has validity test and reliability test using Alpha Cronbach formula. Reliability result is 0,8715. The conclusion shown that research have the difference entrepreneurial intention based on Locus of Control.